Q: If 2 plus 3 equals 10 7 plus 2 equals 63 6 plus 5 equals 66 8 plus 4 equals 96 Then what does 9 plus 7 equal?

Write your answer...

Submit

Related questions

144

144

35

144

63 plus 47 plus 42 plus 21 is equal to 173.

9 plus 7 equals 144. Generally, x plus y = x(x+y).

144

96

26

144 This works if you first add the two digits (ex. 2+3=5), then multiply the first digit by the answer you got (2+5=10).

144 is the answer.2+3=10 which means 2+3=55*2=107+2=63 7+2=99*7=63now 9+7=? 9+7=1616*9=144

If I am correct, 9 plus 7 equals 112.

144 add the two numbers and multiply by the first 2(2 + 3) = 10 7(7 + 2) = 63 etc.

144, you add the plus numbers, then multiply it by the first.

144, you add the plus numbers, then multiply it by the first.

144 (square the first value and add the product of the two values). In the statement 7 + 6 should = 91, not 63, which would be 7 + 2.

144 9+7 = 16 and 9*16 = 144

273 13+8 = 21 and 13*21 = 273

63 +99 ___ 162

2 squared plus 2 x 3 = 10, 7 squared plus 7 x 2 = 63, 6 squared plus 6 x 5 = 66,8 squared plus 8 x 4 = 96 so 9 squared plus 9 x 7 = 81 + 63 = 144.

2+3 = 5 * 2 = 10. 7+2 = 9 * 7 = 63.6+5 = 11 * 6 = 66.x+y = z * x = n.9+7 = 16 * 9 = 144

144 9+7 = 16 and 9*16 = 144

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.

9 plus 7 equals 144. The series is formed by multiplying the first number with the sum of both numbers. 2(2 + 3 ) = 10 : 7(7 + 2) = 63 : 6(6 + 5) = 66 : 8(8 + 4) = 96 : Then 9(9 + 7) = 144.